2012
DOI: 10.1016/j.jchemneu.2011.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Localisation of novel forms of glutamate transporters and the cystine-glutamate antiporter in the choroid plexus: Implications for CSF glutamate homeostasis

Abstract: The choroid plexus is a structure within each ventricle of the brain that is composed of fenestrated vessels surrounded by secretory epithelial cells. The epithelial cells are linked by tight junctions to create a permeability barrier. The epithelial cells are derived from neuroectoderm, and are thus defined by some authors as a subtype of macroglia. Glutamate is a tightly regulated substance in the CSF, as it is in the rest of the brain. In the brain macroglia express multiple sodium dependent and independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…In agreement with an earlier study by Lee et al [39], also Glu transporter EAAT1/GLAST (Slc1a3) mRNA was detected in our study. Recently another glutamate transporter, EAAT3 (Slc1a1), was suggested to be the main Glu transporter in CP based on immunofluorescence and transport studies made in rat [23].…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with an earlier study by Lee et al [39], also Glu transporter EAAT1/GLAST (Slc1a3) mRNA was detected in our study. Recently another glutamate transporter, EAAT3 (Slc1a1), was suggested to be the main Glu transporter in CP based on immunofluorescence and transport studies made in rat [23].…”
Section: Discussionsupporting
confidence: 94%
“…Our in vitro transport studies imply that EAATs are involved in the uptake of L-Glu into CPE and ependymal cells from the CSF via carrier-mediated mechanisms. EAAT1, EAAT3, and xCT have been reported to be expressed in ependymal cells although their localization on ependymal cells has not been fully evaluated [ 22 , 19 ]. From our immunohistochemical study using rat brain sections (Figure 1 A-C), we found that EAAT1 was strongly expressed in ependymal cells relative to CPE cells, and localized on the apical membrane (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Mannitol, D-[1- 14 C] ([ 14 C]D-mannitol, 55 mCi/mmol) and butanol, n [1- 14 C] ([ 14 C] n -butanol, 2 mCi/mmol) were purchased from American Radiolabeled Chemicals (St. Louis, MO, USA). Rabbit anti-EAAT1 antibodies [ 27 ], which recognize EAAT1 and three kinds of splice variants (GLAST1a, GLAST1b, and GLAST1c [ 22 ]), and rabbit anti-EAAT2 antibodies [ 28 ], which recognize EAAT2 and do not bind to other splice variants (GLT-1b, exon 9-skipped GLT-1b, and GLT-1c [ 22 ]), were kindly gifted from Dr. M. Watanabe, Hokkaido University, Sapporo, Japan. All other chemicals were commercial products of analytical grade.…”
Section: Methodsmentioning
confidence: 99%
“…GLAST was found to be present and probably functional at the mammalian neuromuscular junction [45], in the choroid plexus [46] and in other tissues, for example in pancreas [47] and in the heart muscle cells where it may have an important function [48]. GLT and possibly other EAATs exist in testes [49,50] and EAAT5 is present in many peripheral tissues [42,51].…”
Section: Location Of Eaats and Their Possible Roles In Brain Functionsmentioning
confidence: 99%